The Review of Internet Resources on Economic sociology (part 6) – Classics of economic sociology, history and methodology of economic sociology, social stratificationклассика экономической социологии - НовиковаЕлена Геннадьевна (Journal of Economic Sociology, 2010)
Detailed description in the text